2019
DOI: 10.1177/0954407019826475
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence modeling effects on the aerodynamic characterizations of a NASCAR Generation 6 racecar subject to yaw and pitch changes

Abstract: The characterization of a racecar’s aerodynamic behavior at various yaw and pitch configurations has always been an integral part of its on-track performance evaluation in terms of lap time predictions. Although computational fluid dynamics has emerged as the ubiquitous tool in motorsports industry, a clarity is still lacking about the prediction veracity dependence on the choice of turbulence models, which is central to the prediction variability and unreliability for the Reynolds Averaged Navier–Stokes simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Additionally, the DES approach is still cost prohibitive for many applications; for example, for the recently developed DrivAer vehicle, the DES simulation is 17-times more expensive than the RANS computations [2]. In present day high-fidelity CFD analyses, simulations with 120 million cells are very common; even a RANS-based well-converged simulation of this size takes more 3000 core-hours for completion (see [4]), implying that a DES would have taken more than 50,000 core-hours for a single case. This makes the use DES analysis impractical for motorsports applications for sure and may be for the passenger vehicle industries as well.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the DES approach is still cost prohibitive for many applications; for example, for the recently developed DrivAer vehicle, the DES simulation is 17-times more expensive than the RANS computations [2]. In present day high-fidelity CFD analyses, simulations with 120 million cells are very common; even a RANS-based well-converged simulation of this size takes more 3000 core-hours for completion (see [4]), implying that a DES would have taken more than 50,000 core-hours for a single case. This makes the use DES analysis impractical for motorsports applications for sure and may be for the passenger vehicle industries as well.…”
Section: Introductionmentioning
confidence: 99%
“…The additional terms À ru i u j in equation (2) are known as the Reynolds stress terms which are due to the fluctuating velocity field. Using the Reynolds decomposition, a time-dependent quantityã(t) can be decomposed as the sum of its time-averaged value A and a fluctuating component a(t), that is,ã(t) = A + a(t).…”
Section: Rans Sst Transport Equationsmentioning
confidence: 99%
“…As a result, it has become a commonplace to execute scale-resolved (SRS) and scale-averaged (SAS) CFD simulations using over 100 million cells. 1,2 However, existing literature suggests that, in many engineering applications, transient SRS, such as the detached eddy simulation (DES) for short, are viewed by many as the preferred modeling approach over the steady-state Reynolds-averaged Navier–Stokes (RANS) simulations due to its perceived success in providing a better-correlated flow field predictions. These studies found that DES approaches generally perform better than RANS approaches, in terms of predicting integral flow quantities, like force and moment coefficients, and as well as the pressure and velocity fields, especially in the wake region.…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant number of works have been published concerning CFD and wind tunnel correlations [33][34][35][36][37][38][39][40], very few of these studies investigated the comparison among wind tunnel tests with both static floor, rolling-road, and track testing from a numerical investigation point of view. A numerical comparison between different wind tunnel test sections, viz.…”
Section: Introductionmentioning
confidence: 99%